Strategi Pengembangan Dan Inovasi Bisnis UD. Barokah Berbasis Sumberdaya Manusia - Ari Arham Palaguna; Suryadi Samudra; Adfiyani Fadjar (Journal of Management and Social Sciences, 2023)
Development of products and services to the community is the key to success in business ventures. UD. Barokah is a business that is engaged in meeting the primary needs of the community, namely in the form of selling various kinds of products, both in the form of sales of wholesale and retail. Sales have been carried out effectively by utilizing competitive business opportunities with various business plans. In achieving sales targets, UD Barokah carries out various strategies and innovations on an ongoing basis in order to maintain business existence and compete with other entrepreneurs. Efforts to build communication with customers through creating Whatshap groups and services in a timely manner are important keys in attracting and retaining customers.The main objective of this research is to find out the business strategies and innovations implemented by UD Barokah in achieving sales targets. The specific objective of this research is to learn to run a business, find out the factors that influence the development of UD Barokah's business, and make creations and innovations in developing business and market opportunities.